The public-private wage gap in Brazil - Miguel Nathan Foguel; Indermit Singh Gill; Rosane Silva Pinto de Mendonça; Ricardo Paes de Barros (Institute for Applied Economic Research (ipea), 2015)
Recent changes in public employment in Brazil generate costs to workers that leave this sector. In this study we investigate the wage loss that leaving public employees may experience if they were absorbed by the private sector. Using microdata from the Pesquisa Nacional por Amostra de Domicílios of 1995, we calculate the gross and controlled wage gaps between the two sectors. The results show that both wage gaps are relatively high, although significantly lower for the second measure. The latter indicates the presence of important differences in the composition of the labor force between the two sectors. In fact, public employees tend to be on average better educated, older and have longer tenure than the workers in the private sector. Also, the study shows that there is a significant heterogeneity within the public sector: the wage gap is higher for federal public employees, decreasing for the state and municipal levels.
Keywords: 330